(untitled) (Pesquisa Odontológica Brasileira, 2000)
Hereditary gingival fibromatosis (HGF) is a rare oral condition, clinically manifested through a generalized and fibrotic enlargement of the gingiva, which may present as an isolated clinical finding or in association with other features, as part of a syndrome. The biological mechanisms involved in HGF are unknown, and the results of cell-culture studies are controversial. To elucidate the phenotypic and proliferative characteristics of HGF fibroblasts, we isolated 4 cell lines of gingival fibroblasts from members of the same family with HGF, and compared with gingival fibroblasts from 4 healthy patients (NG). HGF and NG fibroblasts, in subconfluent culture densities, showed typical morphological characteristics, such as spindle form with a central spherical nucleus and long cytoplasmatic prolongations, but in saturation density, HGF cells were shorter than control cells. The nucleus/cytoplasm relation was always smaller in all HGF cell lines, suggesting that the cellular reduction is derived from reduction or compaction of the cytoplasm and not of the nucleus. The proliferation rate was higher in fibroblasts from HGF than in the ones from NG. These results suggest that differences in the morphology and proliferation of HGF fibroblasts may be associated with the biological events involved in the pathogenesis of gingival overgrowth in HGF patients.